2022
DOI: 10.1111/dth.15407
|View full text |Cite
|
Sign up to set email alerts
|

Impact on health‐related quality of life and symptoms of anxiety and depression after 32 weeks of Dupilumab treatment for moderate‐to‐severe atopic dermatitis

Abstract: Dupilumab is the first biological agent approved for treatment of moderate-to-severe atopic dermatitis (AD). Evidence of Dupilumab effectiveness on psychological outcomes beyond 16 weeks of treatment from real-life settings is lacking. To evaluate the effectiveness of Dupilumab treatment up to 32 weeks, focusing health-related quality of life and psychological outcome of patients with moderate-to-severe AD. An observational prospective cohort study was conducted in a real-life setting at an Italian tertiary ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Although the detailed molecular mechanism of AD and psychological disorders remains unclear, higher IL-4 and IL-13 serum levels (Th2) were also observed in a group with a major depressive disorder [ 93 ]. Dupilumab treatment impairs anxiety and depressive symptoms [ 94 , 95 ], suggesting the possible importance of systemic therapy against the psychological disorder development in addition to a possible role of Th2 immune response in the pathogenesis of psychological disorders.…”
Section: Depressionmentioning
confidence: 99%
“…Although the detailed molecular mechanism of AD and psychological disorders remains unclear, higher IL-4 and IL-13 serum levels (Th2) were also observed in a group with a major depressive disorder [ 93 ]. Dupilumab treatment impairs anxiety and depressive symptoms [ 94 , 95 ], suggesting the possible importance of systemic therapy against the psychological disorder development in addition to a possible role of Th2 immune response in the pathogenesis of psychological disorders.…”
Section: Depressionmentioning
confidence: 99%
“…Combining dupilumab with a conventional drug or phototherapy is an appropriate and safe therapy option which allows patients recalcitrant to dupilumab monotherapy [ 99 ]. Subsequent real-life studies have confirmed the data from the registration studies in clinical practice, regarding efficacy, safety, and improvement of patient-reported outcomes [ 100 , 101 ]…”
Section: Management Of Atopic Dermatitismentioning
confidence: 79%
“…The biological, clinical, and psychological factors and parameters of AD that correlate with the symptoms of pruritus, particularly during systemic therapy, have not been well-defined yet in the literature on this subject [ 3 ]. Real-life experiences of pruritus during treatment with dupilumab and the possible associated factors are scarce, as well as possible differences between adolescent and adult populations [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%